Underwater photo contests to complement coastal fish inventories: results from two Mediterranean Marine Protected Areas - TIRALONGO, FRANCESCO; La MESA, GABRIELE; PALADINI De MENDOZA, FRANCESCO; MASSARI, FILIPPO; AZZURRO, ERNESTO (Mediterranean Marine Science, 2021)
Assessing fish assemblages and providing reliable fish inventories are tasks of particular relevance for Marine Protected Areas (MPAs). In this study we demonstrated the usefulness of underwater photo contests as complementary tools to accomplish this goal. We examined a total of 3513 underwater pictures taken by both free-diving and SCUBA during two Italian photo contests organized by the Italian Federation of Sport Fishing and Underwater Activities (FIPSAS). The competitions, held during the years 2017-2018, took place in the MPAs of Punta Campanella (Tyrrhenian Sea) and Capo Rizzuto (Ionian Sea). Overall, we identified 97 fish species: 89 at Punta Campanella and 75 at Capo Rizzuto MPA, occurring in a depth range of 0-19 m across different coastal habitats. This number resulted to be considerably higher than that reported with other census techniques and close to the maximum number of species, as evidenced by accumulation curves. Significant differences in species richness were highlighted at the level of both location and habitat type. Reasons of these differences are discussed, along with the advantages and limitations of the underwater photo contest as a participatory tool for gaining regular updates on coastal fish inventories in Marine Protected Areas and beyond.